Desain Arsitektur Jaringan Management Environment Dengan Software Defined Network - Setioutomo, Luthfi; Laksana, Eka Purwa (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2020)
Software Defined Network (SDN) is a new concept and is increasingly being used because of its flexible design and centralized configuration which makes it easy for network administrators in configuring a computer network. With the benefits gained from SDN technology, this research focuses on designing a network management environment architecture using Software Defined Network. The new design is a form of expansion of the old network management environment, where the old and new management environments will be interconnected. Using QoS to be able to compare the quality of each management environment. The expansion of the management environment has reduced the use of management environment capacity from 98% to 75%. The old management environment and the new management environment are well connected. The new management environment has better throughput and jitter values than the old management environment. Whereas the value of the packet loss management new environment is worse than the old management environment. Using SDN technology makes it easy for network administrators to only configure one SDN controller (BCF controller) device.